Investigating the contribution of cytoarchitecture to diffusion MRI measures in gray matter using histology - Baxi, Madhura; Cetin-Karayumak, Suheyla; Papadimitriou, George; Makris, Nikos; van der Kouwe, Andre; Jenkins, Bruce; Moore, Tara L.; Rosene, Douglas L.; Kubicki, Marek; Rathi, Yogesh (Frontiers in Neuroimaging, 2022)
Postmortem studies are currently considered a gold standard for investigating brain structure at the cellular level. However, to investigate cellular changes in the context of human development, aging or disease treatment, noninvasive in-vivo imaging methods such as diffusion MRI (dMRI) are needed. However, dMRI measures are only indirect measures and require validation in gray matter (GM) in the context of their sensitivity to the underlying cytoarchitecture, which has been lacking. Therefore, in this study we conducted direct comparisons between in-vivo dMRI measures and histology acquired from the same 4 rhesus monkeys. Average and heterogeneity of fractional anisotropy and Trace from diffusion tensor imaging and mean squared displacement (MSD) and return-to-origin-probability from biexponential model were calculated in 9 cytoarchitectonically different GM regions using dMRI data. DMRI measures were compared with corresponding histology measures of regional average and heterogeneity in cell area density. Results show that both average and heterogeneity in Trace and MSD measures are sensitive to the underlying cytoarchitecture (cell area density) and capture different aspects of cell composition and organization. Trace and MSD thus would prove valuable as non-invasive imaging biomarkers in future studies investigating GM cytoarchitectural changes related to development and aging as well as abnormal cellular pathologies in clinical studies.